2018
DOI: 10.1186/s12889-018-6273-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of “international transfer-out” among foreign-born pulmonary tuberculosis patients in Japan – what are the implications for a cross-border patient referral system?

Abstract: BackgroundTuberculosis (TB) patients crossing borders pose a serious challenge to global TB control efforts. The objectives of our study were firstly, to evaluate the trend and size of foreign-born pulmonary TB patients, who had been notified and initiated treatment in Japan but have transferred out of the country while still on treatment; and secondly, to conduct a detailed analysis of these patients and identify possible risk factors for international transfer-out, and discuss policy implications for a cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…(national border or boundary) referral or collaboration to improve TB prevention and management, including ensuring continuity of care to achieve favorable TB treatment outcomes [30,31]. TB cases in our study cohort were mostly adult males, a trend similarly observed worldwide [1].…”
Section: Plos Onementioning
confidence: 86%
“…(national border or boundary) referral or collaboration to improve TB prevention and management, including ensuring continuity of care to achieve favorable TB treatment outcomes [30,31]. TB cases in our study cohort were mostly adult males, a trend similarly observed worldwide [1].…”
Section: Plos Onementioning
confidence: 86%
“…However, globally, such attempts are still limited [35]. In Japan, treatment outcomes of those who have transferred out of Japan remain unknown [36], however, recently, a research program has been started to coordinate cross-border referral for patients who were diagnosed as TB in Japan but who have decided to leave Japan to continue treatment elsewhere [37].…”
Section: Discussionmentioning
confidence: 99%